Pengaruh Model Pembelajaran Take And Give terhadap Hasil Belajar Siswa pada Tema 8 Daerah Tempat Tinggalku Subtema 2 Keunikan Daerah Tempat Tinggalku pada Siswa Kelas IV UPTD SD Negeri 122332 Jl. Jend. Sudirman - Mey Linda Arihta Perangin Angin; Lisbet Novianti Sihombing; Hetdy Sitio (Journal on Education, 2023)
This exploration aims to determine the effect of using the take ang give learning model on student learning outcomes on theme 8 of the area where I live, sub-theme 2 of the uniqueness of the area where I live in class IV UPTD SD Negeri 122332 Jl. Gen. Sudirman. This exploration was carried out at UPTD SD Negeri 122332 Jl. Gen. Sudirman in May 2023. The exploration used was quantitative exploration using a Quasi-experiment (pseudo-experiment) with 60 students in class IV-A and IV-B as samples. The variables in this exploration are the take and give model (X) and learning achievement (Y). Methods of data collection by using tests. Data analysis techniques using normality test, homogeneity test, hypothesis testing. Based on the results of the exploration that has been carried out on the test data for the take and give model with a sample of 60 students, then the pre-test score for the experimental class is obtained with an average value of 57.33, the post-test experiment with an average value of 74.66. And the pre-test control class average 50.33 and the control class post-test score with an average value of 67.